1969
DOI: 10.1002/bit.260110608
|View full text |Cite
|
Sign up to set email alerts
|

The production, isolation, and characterization of a grisein‐like sideromycin complex

Abstract: SummaryStreptomyces griseus var. X-2455 produces an antibiotic complex which is active in vitro against a number of gram-positive and gram-negative bacteria and in mice against systemic infections caused by K . pneumoniae and D. pneumoniae. In view of the favorable chemotherapeutic index and the broad in oitro spectrum of crude concentrates, isolation of the pure antibiotic complex and the individual constituents ww undertaken. The antibiotics referred to as Ro 5-2667, Ro 7-7730, and Ro 7-7731 can be different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1970
1970
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Albomycins are broad-spectrum antibiotics that have been isolated several times from soil-dwelling actinomycetes in various drug discovery programs since the first report dating back 60 years . Their extreme antibacterial potency and extended spectrum has prompted numerous attempts to develop albomycins into a commercial drug and likewise spawned a longstanding interest in elucidating the mechanism of action of albomycins . These studies have revealed that albomycins are Trojan horse antibiotics that consist of a ferrichrome-type siderophore component that is indiscriminately taken up by bacteria as a mechanism to scavenge iron from the environment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Albomycins are broad-spectrum antibiotics that have been isolated several times from soil-dwelling actinomycetes in various drug discovery programs since the first report dating back 60 years . Their extreme antibacterial potency and extended spectrum has prompted numerous attempts to develop albomycins into a commercial drug and likewise spawned a longstanding interest in elucidating the mechanism of action of albomycins . These studies have revealed that albomycins are Trojan horse antibiotics that consist of a ferrichrome-type siderophore component that is indiscriminately taken up by bacteria as a mechanism to scavenge iron from the environment.…”
mentioning
confidence: 99%
“…ATCC 700974, the cytosine base carries two modifications: one is methylation of the N3 and the other is carbamoylation of the N4 imino nitrogen. These modifications are known to significantly enhance the bioactivity of albomycins since two minor congeners that either lack the carbamoyl group (albomycin ε) or with the N 3 -methylcytosine substituted by a N 3 -methyluracil (albomycin δ 1 ) have been isolated and assessed . While the C-terminal nonproteinogenic amino acid contains several uncommon features such as a thioether modification of the furanoside and N4-carbamoylation of cytosine, N3-methylated cytosine is found only in eukaryotic tRNAs and rRNAs and is thought to finely modulate structures and functions of the RNAs.…”
mentioning
confidence: 99%
“…In summary, ABM is an antibacterial agent that was chosen for pharmaceutical development long before the genomic era (6,12,13,44). A rational metabolic engineering strategy for increasing ABM production was adopted in this study.…”
Section: Resultsmentioning
confidence: 99%